(untitled) (American Journal of Aquaculture and Animal Science, 2024)
Savanna herbivores’ landscape utilization is influenced by resource requirements and environmental and anthropogenic factors. The study explored the influence of vegetation cover, elevation and slope, cattle encroachment and human activities on common eland landscape utilisation in the Eland Sanctuary Park, Zimbabwe. Presence-only data for the common eland was recorded between January 2022 and December 2022. Ground surveys were carried out once a week, and data on sightings was recorded using a Global Positioning System (GPS) handset. GPS coordinates for human activities and cattle sighted during the survey in the study area were also recorded. Home range sizes for the common eland were calculated using a vector geometry processing tool. Results of the study showed that number of common eland records was higher in the wet season compared to the dry season. However, there was no significant difference in common eland utilization of montane grassland, miombo, Uapaca kirkiana, and mixed vegetation habitat in dry and wet season (p-value = 0.701). Wet season cattle and eland grazing areas overlapped. The study recommends the use of satellite-enabled collars to monitor near-real-time movement patterns of the common eland in the area.